El reciclaje en el proceso de aprendizaje en el área de Entorno Natural y Social en niños de 4 años de la “U.E Miguel Ángel León Pontón”, ciudad de Riobamba. - Guerrero Paredes, Marilin Maide (2023)
After analyzing the research entitled "Recycling in the learning process in the area of Natural and Social Environment in 4-year-old children from the "U.E Miguel Ángel León Pontón”, city of Riobamba, the main objective of the study is to promote recycling in learning processes in the area of Natural and Social Environment. On this basis, a qualitative approach was adopted, non-experimental design, a descriptive level of scientific research, types of research, for example, by objectives, by place and by time; In addition, the interview was applied as a technique and the questionnaire of open questions as an instrument, this was developed by the teachers of Initial II of the parallels "D" and "E" of the aforementioned institution. In this way, all this study has made it possible to demonstrate the great importance of recycling within the educational area, since it is determined that the use of recycled materials allows students to acquire recycling habits, environmental care and ecological awareness of environmental materials. , in which by recycling these resources the educators will be able to carry out various activities that at the same time awaken in the students their creativity, imagination and exploration of the environment, building better knowledge and significant learning, in addition the didactic materials made must be striking, innovative and safe.